Answer:
Clare starts with:
a*x^2 + b*x + c = 0
And she gets to:
(2*a*x + b)^2 = b^2 - 4*a*c
Now we want to show the final steps to solve the equation (isolating x)
First, we apply the square root to both sides:
[tex]\sqrt{(2*a*x + b)^2} = \sqrt{(b^2 - 4*a*c)}[/tex]
Because the square root has two solutions, (one negative and one positive), we will write:
[tex]2*a*x + b = \pm \sqrt{b^2 - 4*a*c}[/tex]
Now we subtract b in both sides:
[tex](2*a*x + b) - b = \pm \sqrt{b^2 -4*a*c} - b[/tex]
[tex]2*a*x = \pm \sqrt{b^2 -4*a*c} - b[/tex]
Now let's divide by 2*a in both sides:
[tex]2*a*x/(2*a) = \frac{\pm \sqrt{b^2 -4*a*c} - b}{2*a}[/tex]
[tex]x = \frac{\pm \sqrt{b^2 -4*a*c} - b}{2*a}[/tex]